Artificial intelligence in type 1 diabetes mellitus - Łoskot, Wiktoria; Szwech, Jan; Matczak, Mateusz; Jasiński, Karol; Broda, Aleksandra; Hoksa, Kacper; Jodłowski, Krzysztof; Dubniewicz, Ewa; Majewska, Paula; Staszek, Alicja (Journal of Education, Health and Sport, 2025)
Type I diabetes is an autoimmune disease in the course of which insulin levels are reduced and hyperglycemia occurs. Treatment options for type I diabetes have changed a lot over time. A large contribution to advances in the field of diabetes treatment has been made by artificial intelligence. Originally, the treatment consisted of multiple finger punctures per day and multiple insulin injections. But now, thanks to artificial intelligence technology, a number of solutions are available including continuous glucose monitors and, based on these, a decision support system. This makes it possible to reduce the number of finger pricks and the frequency of insulin administration. Above that, it makes it possible to tailor the treatment process to the patient, prepare personalized recommendations and respond quickly to changes in serum glucose levels.